Ekstrak Kulit Cocoa (Theobroma cacao, L) Sebagai Disinfektan Penurunan Angka Kuman - Regina Sabilla Yassarah; Payzar Wahyudi; Elanda Fikri; Bambang Yulianto (Poltekkes Kemenkes Semarang, 2026)
Disinfection is a method aimed at reducing or killing harmful microorganisms on certain surfaces or objects to minimize the potential spread of infections and diseases. This study used a quasi-experimental design to evaluate the effectiveness of cocoa husk extract (Theobroma cacao, L.) as a disinfectant in reducing the total microbial count on eating utensils. The research design was implemented using a pretest and posttest method without a control group. After treatment with the cocoa husk extract disinfectant on plates, the total microbial count was measured at concentration variations of 25%, 50%, and 75%. The average microbial reduction recorded was 2.07 colonies/cm² at 25% concentration, 2.2 colonies/cm² at 50% concentration, and 2.3 colonies/cm² at 75% concentration. Plates in the cafeteria of PT. X showed the highest microbial reduction at the 75% concentration. However, this study did not determine specific types of microorganisms, such as Salmonella spp. or other harmful bacteria. Furthermore, the extraction process was not followed by purification and quantitative analysis of bioactive compounds. Therefore, future researchers are recommended to conduct extract purification and active factor analysis to identify the compounds most responsible for antibacterial activity and to establish the most effective concentration.